2010
DOI: 10.2175/193864710798256464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sludge Homogenization Sludge Pre-Conditioning Process for Increased Biogas Cogeneration Potential and Reduced Sludge Yields from Anaerobic Digestion

Abstract: Recently several technologies and process innovations have been proposed to reduce or eliminate the waste activated sludge (WAS) fraction resulting from treatment, or to render it more amenable to anaerobic digestion, a common sludge stabilization step, in order to maximize biogas production and the corresponding potential for energy cogeneration. Under WERF's 05-CTS-3 Evaluation of Processes to Reduce Activated Sludge Solids Generation and Disposal, data collected from the full-scale demonstration of MicroSlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Under mesophilic digestion, HPH+TPAD systems achieved 18.8% improvement while HPH prior to single-stage digestion and TPAD system showed similar improvement in VS reduction with 12.7% and 12% increase over control. Mesophilic HPH system achieved 12.7% higher VS removal compare to the controls which is in agreement with a previous study conducted by Sandino et al (2010). The authors reported 13.0% improvements in VS removals over the control at for and HPH pretreated mesophilic digester fed with mixed sludge at 7 d SRT.…”
Section: Effect Of Pretreatments On Organic Removal Efficiency Of Anasupporting
confidence: 90%
See 2 more Smart Citations
“…Under mesophilic digestion, HPH+TPAD systems achieved 18.8% improvement while HPH prior to single-stage digestion and TPAD system showed similar improvement in VS reduction with 12.7% and 12% increase over control. Mesophilic HPH system achieved 12.7% higher VS removal compare to the controls which is in agreement with a previous study conducted by Sandino et al (2010). The authors reported 13.0% improvements in VS removals over the control at for and HPH pretreated mesophilic digester fed with mixed sludge at 7 d SRT.…”
Section: Effect Of Pretreatments On Organic Removal Efficiency Of Anasupporting
confidence: 90%
“…TWAS at higher concentrations could achieve significant reduction in electrical energy consumption as well as total input energy requirement. At full-scale applications, a TWAS with TS concentration of 6 to 10% was reported to be processed by a HPH system without major limitation (Sandino et al 2010). For example, a TS concentration of 7.5% could reduce the total input energy from 4.46 to 2.20 GJ/tonne TCOD fed (about 51% less).…”
Section: Energy Assessment For Full-scale Digestion Scenariosmentioning
confidence: 99%
See 1 more Smart Citation